Integrating Local Wisdom in Independent Learning: Urgency and Innovative Strategies - Tito Pangesti Adji; Shufa, Naela Khusna Faela (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2024)
This study examines the importance of integrating local wisdom into learning and explores innovative strategies that teachers can use to develop students with strong character and essential 21st-century skills. Using a qualitative method with a case study approach, the research was conducted in primary schools in Pati and Demak Regencies, including SDN Bintoro 5, SD Plus Latansa, SDN 5 Gembong, and SDN 2 Cluwak. Data was collected through interviews, documentation, and observations, then analyzed using a qualitative descriptive approach. The results show that 75% of teachers responded positively to the integration of local wisdom, which enhances the relevance, engagement, and meaning of learning materials, while also boosting student motivation and essential skills. Teachers can promote this approach by analyzing learning difficulties, identifying local strengths, and designing lessons with appropriate methods and models. Recommended learning models include problem-based learning, STEAM based on Project-Based Learning, and Contextual Teaching and Learning (CTL), all of which have been shown to improve educational outcomes.